2017
DOI: 10.1111/jcpe.12747
|View full text |Cite
|
Sign up to set email alerts
|

Hard and soft tissue integration of immediate and delayed implants with a modified coronal macrodesign: Histological, micro‐CT and volumetric soft tissue changes from a pre‐clinical in vivo study

Abstract: Triangular implants showed similar percentage of osseointegration, buccal bone volume and soft tissue contours, although attaining greater buccal crestal bone width. No differences were found in regard to soft tissue dimensions and the position of the first bone-to-implant contact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 44 publications
1
23
1
Order By: Relevance
“…Factors such as implant diameter and implant position (Caneva et al, ), the thickness of the buccal bone plate (Araujo, Wennstrom, & Lindhe, ), flapless versus flapped surgical intervention (Blanco, Nunez, Aracil, Munoz, & Ramos, ), or the use of biomaterials filling the gap (Araujo, Linder, & Lindhe, ) are known factors that may influence the vertical resorption of the buccal bone wall. Results from the present investigation are in partial disagreement with those reported in a recent publication using a similar study design but aimed to evaluate the influence of a new implant coronal geometry, where the observed vertical buccal bone resorption ranged between 1 and 1.5 mm at both immediate and delayed implant sites (Sanz‐Martin et al, ). The longer healing period may in part explain these differences.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Factors such as implant diameter and implant position (Caneva et al, ), the thickness of the buccal bone plate (Araujo, Wennstrom, & Lindhe, ), flapless versus flapped surgical intervention (Blanco, Nunez, Aracil, Munoz, & Ramos, ), or the use of biomaterials filling the gap (Araujo, Linder, & Lindhe, ) are known factors that may influence the vertical resorption of the buccal bone wall. Results from the present investigation are in partial disagreement with those reported in a recent publication using a similar study design but aimed to evaluate the influence of a new implant coronal geometry, where the observed vertical buccal bone resorption ranged between 1 and 1.5 mm at both immediate and delayed implant sites (Sanz‐Martin et al, ). The longer healing period may in part explain these differences.…”
Section: Discussioncontrasting
confidence: 83%
“…The surgical protocol has been described in detail in a previous report (Sanz‐Martin et al, ). This first intervention consisted on the extraction of first premolar (1P1) and the extraction of the mesial roots of the second premolar and first molar (2P2 and 1M1) after their hemi‐section.…”
Section: Methodsmentioning
confidence: 99%
“…However, the neo-formed bone filling the gaps needs time to mature into cortical bone (Berglundh, Abrahamsson, Lang, & Lindhe, 2003). Using a dog model, Sanz-Martin et al (2017) recently showed that at 4 weeks-most gaps between the TN implant and the bone were filled by immature cortical bone and were completely filled after 12 weeks of healing. This result still needs to be verified in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental study was carried out at the Experimental Surgical Centre of the Hospital “Gomez‐Ulla” in Madrid, Spain, once the Regional Ethical Committee for Animal Research approved the study protocol (Code: ES280790000187). This investigation reports the results from a subset analysis of the specimens whose histological results are reported in a separate publication (Sanz‐Martin et al, ).…”
Section: Methodsmentioning
confidence: 99%